IMPROVING THE ACCOUNTING OF CORPORATE DIVISION, SPIN-OFF AND TRANSFORMATION OF LEGAL FORM PROCESSES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the theoretical and methodological aspects of accounting and financial reporting for enterprise reorganization processes, including division, spin-off, and transformation of legal form. Recommendations are developed for the valuation, allocation, and transfer of assets, liabilities, and equity to successor entities. The proposed approaches contribute to improving the reliability and transparency of accounting information.
Keywords: Reorganization, division, spin-off, transformation of legal form, accounting, financial reporting, succession, valuation differences, allocation balance sheet.